Pengaruh Lingkungan Kerja Terhadap prestasi Kerja Karyawan Pada KSPPS BMT Amanah Ray - irfan irfan; Ahmad Albar Tanjung (CIVITAS: Jurnal Studi Manajemen, 2022)
This study was to aims to determine whether there was an influence of the work environment on employee work performance on KSPPS BMT Amanah Ray. The sample of this study was 30 employees of KSPPS BMT Amanah Ray. Sampling used saturated sampling techniques, namely sampling techniques where all members of the population are sampled. Data analysis used a simple regression test, testing the hypothesis using the test coefficient of determination (R2), partial test (t test). while processing data using SPSS 20. The results of this study indicate that the work environment variable was able to explain the variations that occur in employee work performance, in addition partially the work environment variable has a significant and significant influence on employee performance on KSPPS BMT Amanah Ray.